The Existence of Positive Solutions for Boundary Value Problem of Nonlinear Fractional Differential Equations - Yanli Chen; Yongxiang Li (Abstract and Applied Analysis)
We consider the existence of positive solutions for the nonlinear fractional differential equations boundary value problem -D0+αu(t)=f(t,u(t)),   0<t<1,  u(0)=u'(0)=u'(1)=0, where 2<α≤3 is a real number, D0+α is the Riemann-Liouville fractional derivative of order α, and f is a given continuous function. Our analysis relies on the fixed point index theory in cones.